The World Price of Earnings Opacity - Bhattacharya, Utpal; Daouk, Hazem; Welker, Michael (The Accounting Review, 2003)
We analyze financial statements from 34 countries for the period 1984–1998 to construct a panel data set measuring three dimensions of reported accounting earnings for each country: earnings aggressiveness, loss avoidance, and earnings smoothing. We hypothesize that these three dimensions are associated with uninformative or opaque earnings, and so we combine these three measures to obtain an overall earnings opacity time-series measure per country. We then explore whether our three measures of earnings opacity affect two characteristics of an equity market in a country: the return the shareholders demand and how much they trade. While not all results are consistent for our three individual earnings opacity measures, our panel data tests document that, after controlling for other influences, an increase in overall earnings opacity in a country is linked to an economically significant increase in the cost of equity and an economically significant decrease in trading in the stock market of that country.